ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN STATUS IMUNISASI DASAR BAYI 9-12 BULAN DI WILAYAH KERJA PUSKESMAS SIKUMANA KOTA KUPANG - Lidwina Dewy Yuliana; Herliana Monica Azi Djogo; Maria Lupita Nena Meo (CHMK Applied Science Journal, 2020)
ABSTRACT Background. Immunization as a preventive way to prevent infectious diseases. Aim. This study aims to analyze the factors associated with infant basic immunization status (9-12 months) in the Work Area of Sikumana Health Center, Kupang City. Method. The design of this study was quantitative by using a cross sectional study design. Sampling in this study uses purposive sampling with a total sample of 116 respondents, this research instrument uses a questionnaire sheet. Results. The results of this study showed that the majority of respondents had the support of health workers by percentage (63.6%), distance to health facilities was less than 1 km by percentage (62.7%), mother's education (basic) by percentage (62.7%) , and most of the respondents 'knowledge of mothers are in the good category with a percentage (70.9%), occupational mothers who work with a percentage (63.6%), and the majority of respondents' attitudes or behaviors are in the poor category with a percentage (58.2% ) and infant immunization status is incomplete with a percentage (56.4%). Based on the Chi Square statistical test results found that there are 3 factors related to the basic immunization status of infants (9-12 months), namely maternal education with a result of p = 0.019 where p <0.05, maternal employment factors with a result of p = 0.062 where p <0, 05 and maternal behavior (attitude) with the result p = 0.075 where p <0.05. It is hoped that health workers pay more attention and increase the knowledge of mothers about infant immunization, and coordinate with Posyandu cadres related to the immunization schedule. Keywords: Basic Immunization Status, Babies 9-12 months, Sikumana Health Center